Robust Demarcation of the Family Caryophanaceae (Planococcaceae) and Its Different Genera Including Three Novel Genera Based on Phylogenomics and Highly Specific Molecular Signatures - Gupta, Radhey S.; Patel, Sudip (Frontiers in Microbiology, 2020)
The family Caryophanaceae/Planococcaceae is a taxonomically heterogeneous assemblage of >100 species classified within 13 genera, many of which are polyphyletic. Exhibiting considerable phylogenetic overlap with other families, primarily Bacillaceae, the evolutionary history of this family containing the potent mosquitocidal species Lysinibacillus sphaericus, remains incoherent. To develop a reliable phylogenetic and taxonomic framework for the family Caryophanaceae/Planococcaceae and its genera, we report comprehensive phylogenetic and comparative genomic analyses on 124 genome sequences from all available Caryophanaceae/Planococcaceae and representative Bacillaceae species. Phylogenetic trees were constructed based on multiple datasets of proteins including 819 core proteins for this group and 87 conserved Firmicutes proteins. Using the core proteins, pairwise average amino acid identity was also determined. In parallel, comparative analyses on protein sequences from these species have identified 92 unique molecular markers (synapomorphies) consisting of conserved signature indels that are specifically shared by either the entire family Caryophanaceae/Planococcaceae, enabling its reliable demarcation in molecular terms, as well different monophyletic clades present within this family. Based on multiple lines of investigations, 18 monophyletic clades can be reliably distinguished within the family Caryophanaceae/Planococcaceae based on their phylogenetic affinities and identified molecular signatures. Some of these clades are comprised of species from several polyphyletic genera within this family as well as other families. Based on our results, we are proposing the creation of three novel genera within the family Caryophanaceae/Planococcaceae, namely Metalysinibacillus gen. nov., Metasolibacillus gen. nov., and Metaplanococcus gen. nov., as well as transfer of 25 misclassified species from the families Caryophanaceae/Planococcaceae and Bacillaceae into these three genera and in Planococcus, Solibacillus, Sporosarcina and Ureibacillus genera. These amendments establish a coherent taxonomy and evolutionary history for the family Caryophanaceae/Planococcaceae, and the described molecular markers provide novel means for diagnostic, genetic and biochemical studies. Lastly, we are also proposing a consolidation of the family Planococcaceae within the emended family Caryophanaceae.